LEGAL PROBLEMS FOR QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS) USERS IN ONLINE PAYMENT TRANSACTIONS - Pattynama, Francis Maryanne; Santoso, Hardi Anugrah; Miarsa, Fajar Rachmad Dwi; Pribadi, Teguh (ANAYASA : Journal of Legal Studies, 2024)
This research aims to contribute knowledge about the legal protection of QRIS-based online payment systems in the modern era through the development of information and technology in the world of digital commerce. This is certainly the background of various unlawful actions against the use of fake QRIS codes, where perpetrators manipulate the printed barcode scans to be incompatible with the original QRIS owner. In the preparation of this article, the research method used is use normative juridical method where the focus of the problems discussed as data material refers to legal principles and norms that have been contained in related laws and regulations. The results of this study show that the legal regulation procedure for online transactions through the QRIS system is considered to lack proper regulations on the protection of users or business actors. All forms of regulations that regulate several legal products that lead to online transactions such as QRIS need to be updated to become an accurate legal umbrella for online-based transactions that have developed today.